Tìm x,biết :
\(\dfrac{1}{6} + \dfrac{-5}{7} : x = \dfrac{-7}{8}\)
Tìm x biết: x - 1 = \(\dfrac{6}{7}\) + \(\dfrac{1}{7}\) x\(\dfrac{2}{7}\) + \(\dfrac{1}{7}\) x \(\dfrac{5}{7}\)
\(\Rightarrow x-1=\dfrac{6}{7}+\dfrac{1}{7}\times\left(\dfrac{2}{7}+\dfrac{5}{7}\right)=\dfrac{6}{7}+\dfrac{1}{7}\times1\\ \Rightarrow x-1=\dfrac{6}{7}+\dfrac{1}{7}=1\\ \Rightarrow x=1+1=2\)
tìm x
a) \(1\dfrac{1}{2}:x=\dfrac{1}{2}\) b)\(\dfrac{7}{9}-x=\dfrac{2}{3}\) c)\(\dfrac{8}{7}:x=\dfrac{6}{7}\) d)\(\dfrac{9}{5}-x=\dfrac{3}{7}\)
a) \(\Leftrightarrow\dfrac{3}{2}:x=\dfrac{1}{2}\\ \Leftrightarrow x=\dfrac{3}{2}:\dfrac{1}{2}\\ \Leftrightarrow x=3\)
b) \(\Leftrightarrow x=\dfrac{7}{9}-\dfrac{2}{3}\\ \Leftrightarrow x=\dfrac{1}{9}\)
c) \(\Leftrightarrow x=\dfrac{8}{7}:\dfrac{6}{7}\\ \Leftrightarrow x=\dfrac{4}{3}\)
d) \(\Leftrightarrow x=\dfrac{9}{5}-\dfrac{3}{7}\\ \Leftrightarrow x=\dfrac{48}{35}\)
a) x = 3
b) x = \(\dfrac{1}{9}\)
c) x = \(\dfrac{4}{3}\)
d)\(\dfrac{48}{35}\)
Tìm x, biết :
\(a.3\dfrac{4}{5}:40\dfrac{8}{15}=0,25:x\)
\(b.\left(x+1\right):\dfrac{5}{6}=20:3\)
\(c.\dfrac{7}{x-1}=\dfrac{x+1}{9}\)
a: Ta có: \(\dfrac{1}{4}:x=3\dfrac{4}{5}:40\dfrac{8}{15}\)
\(\Leftrightarrow x=\dfrac{1}{4}\cdot\dfrac{\dfrac{608}{15}}{3+\dfrac{4}{5}}\)
\(\Leftrightarrow x=\dfrac{152}{15}:\dfrac{19}{5}=\dfrac{8}{3}\)
b: Ta có: \(\left(x+1\right):\dfrac{5}{6}=\dfrac{20}{3}\)
\(\Leftrightarrow x+1=\dfrac{50}{9}\)
hay \(x=\dfrac{41}{9}\)
c: Ta có: \(\dfrac{7}{x-1}=\dfrac{x+1}{9}\)
\(\Leftrightarrow x^2-1=63\)
\(\Leftrightarrow x^2=64\)
hay \(x\in\left\{8;-8\right\}\)
c. \(\dfrac{7}{x-1}=\dfrac{x+1}{9}\)
\(7.9=\left(x-1\right).\left(x+1\right)\)
\(63=x^2-1\)
\(x^2=63+1\)
\(x^2=64\)
\(x^2=8^2\)
\(x=8\)
1/Thực hiện phép tính:
𝒂) ( \(\dfrac{7}{5}\) − \(\dfrac{8}{7}\) ) + \(3\dfrac{2}{5}\) ∶ 𝟎,𝟔
b) \(\dfrac{11}{6}\) + \(\dfrac{7}{6}\) ∶ \(\dfrac{-5}{4}\)
c) \(\dfrac{7}{4}\) − \(\dfrac{5}{4}\) . \(\dfrac{8}{15}\)
2/ Tìm x biết
b) 𝒙 + 𝟐,𝟓 = \(\dfrac{-8}{3}\)
b) 𝟐𝒙 − 𝟐𝟎% = \(\dfrac{9}{5}\)
𝒄) ( \(\dfrac{5}{4}\) )2 + 𝒙 = \(2\dfrac{3}{4}\)
\(1\)/
\(a\)) \(=\left(\dfrac{7}{5}-\dfrac{8}{7}\right)+\dfrac{17}{5}:0,6\)
\(=\dfrac{9}{35}+\dfrac{17}{3}\)
\(=\dfrac{622}{105}\)
\(b\)) \(=\dfrac{11}{6}+\dfrac{-14}{15}\)
\(=\dfrac{9}{10}\)
\(c\)/ \(=\dfrac{7}{4}-\dfrac{2}{3}\)
\(=\dfrac{13}{12}\)
Câu 1 : Biết\(\dfrac{x}{t}=\dfrac{5}{6};\dfrac{y}{z}=\dfrac{1}{5};\dfrac{z}{x}=\dfrac{7}{3}\) ( x; y; z; t khác 0 ). Hãy tìm tỉ số \(\dfrac{t}{y}\)
A. \(\dfrac{t}{y}=\dfrac{14}{25}\) B. \(\dfrac{t}{y}=\dfrac{7}{8}\) C. \(\dfrac{t}{y}=\dfrac{18}{7}\) D. \(\dfrac{t}{y}=\dfrac{6}{7}\)
Tìm x biết: a) \(\dfrac{6}{-x}=\dfrac{x}{-24}\) b) \(x-\dfrac{7}{12}x+\dfrac{3}{8}x=\dfrac{5}{24}\)
c)\(\left(x-\dfrac{1}{3}\right)^2-\dfrac{1}{2}=1\dfrac{3}{4}\) d) \(\dfrac{x-3}{-2}=\dfrac{-8}{x-3}\)
e) \(\dfrac{9}{x}=\dfrac{-35}{105}\) f) \(\left(x-\dfrac{1}{2}\right)\left(-3-\dfrac{x}{2}\right)=0\)
a: =>6/x=x/24
=>x^2=144
=>x=12 hoặc x=-12
b: =>x(1-7/12+3/8)=5/24
=>x*19/24=5/24
=>x=5/24:19/24=5/19
c: =>(x-1/3)^2=1+3/4+1/2=9/4
=>x-1/3=3/2 hoặc x-1/3=-3/2
=>x=11/6 hoặc x=-7/6
d: =>(x-3)^2=16
=>x-3=4 hoặc x-3=-4
=>x=-1 hoặc x=7
e: =>9/x=-1/3
=>x=-27
f: =>x-1/2=0 hoặc -x/2-3=0
=>x=1/2 hoặc x=-6
Tìm x, biết:
a) \(\dfrac{-1}{10}\) + \(\dfrac{2}{5}\)x + \(\dfrac{7}{20}\) = \(\dfrac{1}{10}\)
b) \(\dfrac{1}{3}\) + \(\dfrac{1}{2}\) : x= \(-\dfrac{1}{5}\)
c) \(-\dfrac{2}{3}\) : x + \(\dfrac{5}{8}\) = \(-\dfrac{7}{12}\)
a, - \(\dfrac{1}{10}\) + \(\dfrac{2}{5}\)\(x\) + \(\dfrac{7}{20}\) = \(\dfrac{1}{10}\)
\(\dfrac{2}{5}\)\(x\) = \(\dfrac{1}{10}\) - \(\dfrac{7}{20}\) + \(\dfrac{1}{10}\)
\(\dfrac{2}{5}\) \(x\) = - \(\dfrac{3}{20}\)
\(x\) = - \(\dfrac{3}{20}\): \(\dfrac{2}{5}\)
\(x\) = - \(\dfrac{3}{8}\)
b, \(\dfrac{1}{3}\) + \(\dfrac{1}{2}\): \(x\) = - \(\dfrac{1}{5}\)
\(\dfrac{1}{2}\): \(x\) = - \(\dfrac{1}{5}\) - \(\dfrac{1}{3}\)
\(\dfrac{1}{2}\): \(x\) = - \(\dfrac{8}{15}\)
\(x\) = \(\dfrac{1}{2}\): (- \(\dfrac{8}{15}\))
\(x\) = - \(\dfrac{15}{16}\)
c, - \(\dfrac{2}{3}\): \(x\) + \(\dfrac{5}{8}\) = - \(\dfrac{7}{12}\)
\(\dfrac{2}{3}\): \(x\) = \(\dfrac{7}{12}\) + \(\dfrac{5}{8}\)
\(\dfrac{2}{3}\) : \(x\) = \(\dfrac{29}{24}\)
\(x\) = \(\dfrac{2}{3}\) : \(\dfrac{29}{24}\)
\(x\) = \(\dfrac{16}{29}\)
Tìm x, biết:
a) \(\dfrac{3}{7}\)x - 0,4 = \(\dfrac{-17}{35}\)
b) 0,2. (x - 3) + 2,4= 10
c) (x : 2,2) . \(\dfrac{1}{6}\) = \(\dfrac{-3}{8}\) . (0,5 - \(1\dfrac{3}{5}\))
a, \(\dfrac{3}{7}\)\(x\) - 0,4 = - \(\dfrac{17}{35}\)
\(\dfrac{3}{7}\)\(x\) = - \(\dfrac{17}{35}\) + 0,4
\(\dfrac{3}{7}\)\(x\) = - \(\dfrac{3}{35}\)
\(x\) = - \(\dfrac{3}{35}\): \(\dfrac{3}{7}\)
\(x\) = - \(\dfrac{1}{5}\)
b, 0,2.(\(x\) - 3) +2,4 = 10
0,2.(\(x\) - 3) = 10 - 2,4
0,2.(\(x\) - 3) = 7,6
\(x\) - 3 = 7,6:0,2
\(x\) - 3 = 38
\(x\) = 38 + 3
\(x\) = 41
\(\dfrac{3}{7}x-0,4=\dfrac{-17}{35}\)
\(\dfrac{3}{7}x=\dfrac{-17}{35}+0,4=\dfrac{-34}{70}+\dfrac{28}{70}\)
\(\dfrac{3}{7}x=\dfrac{-6}{70}=\dfrac{-3}{35}\)
\(x=\dfrac{-3}{35}:\dfrac{3}{7}=\dfrac{-3}{35}\cdot\dfrac{7}{3}\)
\(x=\dfrac{3\cdot\left(-1\right)\cdot7}{5\cdot7\cdot3}=-\dfrac{1}{5}\)
b) \(0,2\left(x-3\right)+2,4=10\)
\(0,2\left(x-3\right)=10-2,4=7,6\)
\(x-3=7,6:0,2=38\)
\(x=38+3=41\)
c) \(\left(x:2,2\right)\cdot\dfrac{1}{6}=\dfrac{-3}{8}\cdot\left(0,5-1\dfrac{3}{5}\right)\)
\(\left(x:2,2\right)\cdot\dfrac{1}{6}=\dfrac{-3}{8}\cdot\dfrac{-11}{10}\)
\(x:2,2=\dfrac{-3}{8}\cdot\dfrac{-11}{10}\cdot\dfrac{6}{1}\)
\(x:2,2=\dfrac{-3\cdot\left(-11\right)\cdot2\cdot3}{2\cdot4\cdot10\cdot1}=\dfrac{99}{40}\)
\(x=\dfrac{99}{40}\cdot2,2=\dfrac{99}{40}\cdot\dfrac{22}{10}\)
\(x=\dfrac{99\cdot2\cdot11}{40\cdot2\cdot5}=\dfrac{1089}{200}\)
Tìm x, biết:
a) \(\dfrac{1}{20}\) - (x - \(\dfrac{8}{5}\)) = \(\dfrac{1}{10}\)
b) \(\dfrac{7}{4}\) - (x + \(\dfrac{5}{3}\)) = \(\dfrac{-12}{5}\)
c) x - [\(\dfrac{17}{2}\) - \(\left(\dfrac{-3}{7}+\dfrac{5}{3}\right)\)] = \(\dfrac{-1}{3}\)
a) 1/20 - (x - 8/5) = 1/10
x - 8/5 = 1/20 - 1/10
x - 8/5 = -1/20
x = -1/20 + 8/5
x = 31/20
b) 7/4 - (x + 5/3) = -12/5
x + 5/3 = 7/4 + 12/5
x + 5/3 = 83/20
x = 83/20 - 5/3
x = 149/60
c) x - [17/2 - (-3/7 + 5/3)] = -1/3
x - (17/2 - 26/21) = -1/3
x - 305/42 = -1/3
x = -1/3 + 305/42
x = 97/14
bài 1 : Tìm y
\(\dfrac{7}{8}xy-\dfrac{6}{4}=\dfrac{3}{2}\) \(\dfrac{2}{5}:y+\dfrac{1}{5}:y=\dfrac{10}{3}\)
bài 2 : Tính nhanh
\(\dfrac{2}{5}x\dfrac{4}{7}+\dfrac{2}{5}x\dfrac{3}{7}\) \(\dfrac{2}{9}:\dfrac{2}{3}:\dfrac{3}{9}\)
Bài 1:
+) \(\dfrac{7}{8}\times y=\dfrac{3}{2}+\dfrac{6}{4}=3\)
\(y=3:\dfrac{7}{8}=\dfrac{24}{7}\)
+) \(\dfrac{1}{y}\times\left(\dfrac{2}{5}+\dfrac{1}{5}\right)=\dfrac{10}{3}\)
\(\dfrac{1}{y}=\dfrac{10}{3}:\dfrac{3}{5}=\dfrac{50}{9}\)
\(y=\dfrac{9}{50}\)
Bài 2:
+) \(=\dfrac{2}{5}\times\left(\dfrac{4}{7}+\dfrac{3}{7}\right)\)
\(=\dfrac{2}{5}\times\dfrac{7}{7}=\dfrac{2}{5}\)
+) \(\dfrac{2}{9}:\dfrac{2}{3}:\dfrac{3}{9}\)
\(\dfrac{2}{9}\times\dfrac{3}{2}\times\dfrac{9}{3}=1\)